EKUALISASI SPT MASA PPN DAN SPT MASA PPh DENGAN SPT TAHUNAN PPh TERHADAP KEWAJIBAN PERPAJAKAN CV. ABADI - Leny Karunianing Sayekti; Bayu Sarjono (Jurnal Bisnis Terapan, 2022)
Abstract In using the self-assessment method, it is possible for taxpayers to make mistakes in fulfilling their tax obligations. The existence of this error resulted in the issuance of a Request for Explanation of Data and /or Information (SP2DK). In 2022 CV. ABADI receives SP2DK from the Pratama Tax Office where the Taxpayer is registered. In the request for explanation letter, the PratamaTax Office found a discrepancy between the Financial Statements reported in the Annual Income Tax Return of the Corporate Income Tax Year 2019 and the reporting of the Period Tax Return which includes the VAT Period Tax Return, Article 23 Income Tax Period Tax Return, and Article 4 paragraph (2) Income Tax Period Tax Return. The difference in income or turnover reported from January – December between the VAT Period Tax Return and the Annual Corporate Income Tax Return amounted to Rp 3,919,090. Then the difference in the fees that should be charged by Income Tax Article 23 and Income Tax Article 4 paragraph (2) which have been reported in the Annual Income Tax Return of the Agency but have not been deducted and reported on the Income Tax Period SPT Article 23 and Income Tax Article 4 paragraph (2) is Rp. 125,550,250 and Rp. 63,409,435. After equalizing, taxpayer can find out the cause of the difference then correct the Annual Income Tax Return of the Agency and the Periodic Tax Return.